KESADARAN MASYARAKAT DAN POLUSI SAMPAH - Muhammad Rais Rahmat Razak; Haeruddin Syarifuddin; Fitriyani Fitriyani; Abdul Jabbar; Muhammad Ikbal (NUSANTARA : Jurnal Ilmu Pengetahuan Sosial, 2020)
The problem of waste, remains an interesting issue to be discussed both among the government and the community. The Adipura Award, which has been contested for years by the government, remains an arena of prestige for the regency and city governments, but Adipura is not the only guarantee of public awareness of waste pollution. Sidrap after receiving the adipura award three times, still found a low level of public awareness of waste pollution. This study aims to determine public awareness, waste pollution and the effect of public awareness on waste pollution in Rappang Village, Panca Rijang District, Sidenreng Rappang Regency. This type of research is quantitative descriptive. The results showed that public awareness and waste pollution are still in the poor category. And public awareness has a significant influence on waste pollution conditions. The village government still needs a lot of socialization to the public about the importance of improving behavior in maintaining environmental health.